2021
DOI: 10.1016/j.indcrop.2020.113084
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of biomass and nutrient accumulation in rubber (Hevea brasiliensis) plantations established on two soil types: Implications for nutrient management over the immature phase

Abstract: Rubber trees are the main source of natural rubber (NR). The area occupied by rubber plantations rose from 3.9 million ha in 1961 to 12.5 million ha in 2018. Both the expansion of rubber plantations in marginal zones (prone to biotic and abiotic stress), and long-term rubber tree cultivation in traditional areas, raise questions about the sustainability of NR production in a context of climate change. Our study set out to gain insights into the biogeochemical cycles in rubber plantations, for a better matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Secondly, the defoliation (leaf offset), also referred to as "wintering", is usually seen in rubber trees once they are matured, that is, once they are greater than 4 years old [50][51][52]. In the Northern Hemisphere, specifically in mainland Asia (e.g., Cambodia and Thailand), rubber plantations have been observed to be in dormancy (LAI = 0) for about three weeks in January [11].…”
Section: Phenology Scheme For Rubbermentioning
confidence: 99%
“…Secondly, the defoliation (leaf offset), also referred to as "wintering", is usually seen in rubber trees once they are matured, that is, once they are greater than 4 years old [50][51][52]. In the Northern Hemisphere, specifically in mainland Asia (e.g., Cambodia and Thailand), rubber plantations have been observed to be in dormancy (LAI = 0) for about three weeks in January [11].…”
Section: Phenology Scheme For Rubbermentioning
confidence: 99%
“…Wood biomass removal is known to be detrimental to soil quality (Hardiyanto & Sadanandan Nambiar, 2014; Perron, Kouakou, et al, 2021). According to Perron, Mareschal, et al (2021), exporting biomass may lead to a critical lack of nutrients in rubber plantations. Fertilization practices may overcome this loss for the second rotation but may not be sufficient to restore overall soil characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Planting cover crops, typically legumes, can improve soil physical and chemical properties, leading to an improvement in soil function and crop yield in tropical regions (Snapp et al 2005;Gao et al 2017). Perron et al (2021) suggested that a potential alternative for restoring soil functions is to leave logging residues due to the large amounts of nutrients and carbon they contain. Logging residues play important ecological roles in maintaining plantation fertility in various soil and climate systems, such as reducing chemical fertilizer use, increasing soil carbon sequestration, promoting soil nitrogen cycling (Arcand et al 2014) and preventing environmental pollution from burning (Ibrahim et al 2015).…”
Section: Introductionmentioning
confidence: 99%